Review on synthesis of 3D graphene-based configurations and their adsorption performance for hazardous water pollutants - Hiew, Billie Yan Zhang; Lee, Lai Yee; Lee, Xin Jiat; Thangalazhy-Gopakumar, Suchithra; Gan, Suyin; Lim, Siew Shee; Pan, Guan Ting; Yang, Thomas Chung Kuang; Chiu, Wee Siong; Khiew, Poi Sim (Institution of Chemical Engineers, 2018)
Water pollution is a global health and environmental issue affecting all life forms. The treatment of water polluted by dyes, heavy metals and pharmaceuticals is a major challenge to operators of wastewater treatment facilities. Adsorption technology functions effectively in removing these pollutants using specific adsorbents. Graphene oxide (GO) and its three dimensional (3D) configurations are new carbon-based adsorbents. With superiorly large surface area, high porosity and large variety of functional groups, these materials have been tested for their potential application in wastewater treatment. This review focuses on the synthesis methods of 3D graphene-based structures and their adsorption performance of dyes, heavy metals and pharmaceuticals. Various synthesis methods have been successfully developed demonstrating the feasibility of configuring graphene into porous 3D networks. These methods can be categorised into direct synthesis and solution-based methods. The 3D graphene structures portrayed relatively high adsorption capacities for the three pollutant groups. Their adsorptive properties were influenced by characteristics of pollutant, adsorbent surface and process parameters. The major adsorption mechanisms of the 3D graphene-based structures were identified to be hydrogen bonding, electrostatic, π-π and hydrophobic interactions. This review indicated that 3D graphene configurations are promising solutions for practical application of carbon nanomaterials in wastewater treatment.